Perancangan Sistem Informasi Akuntansi Harga Pokok Produksi Pada Distro Viking Cimahi Dengan Menggunakan Software Microsoft Visual Basic 2008 Dan Database MySQL - Sheylla Febryani; Dony Waluya Firdaus (Labkat Press KA FTIK UNIKOM, 2019)
Viking Distro cimahi conducts business in manufacturing companies that produce t-shirts for Persib bandung soccer players, researchers conducted a survey and found that the accounting records system that is currently running is still manual, therefore researchers conducted research with the title